2005
DOI: 10.1007/s00109-005-0658-0
|View full text |Cite
|
Sign up to set email alerts
|

Single-nucleotide polymorphisms in the C-reactive protein (CRP) gene promoter that affect transcription factor binding, alter transcriptional activity, and associate with differences in baseline serum CRP level

Abstract: To investigate whether functional polymorphisms exist in the C-reactive protein (CRP) gene, i.e., ones that contribute directly to differences in baseline CRP among individuals, we sequenced a 1,156-nucleotide-long stretch of the CRP gene promoter in 287 ostensibly healthy people. We identified two single-nucleotide polymorphisms (SNPs), a bi-allelic one at nucleotide -409 (G-->A), and a tri-allelic one at -390 (C-->T-->A), both resident within the hexameric core of transcription factor binding E-box elements.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
128
1
5

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(144 citation statements)
references
References 33 publications
10
128
1
5
Order By: Relevance
“…We also examined whether these polymorphisms had any effect on serum CRP levels, and found that basal levels of CRP were significantly higher in individuals who had minor allele in -390 C>A or T and 2043 A>G polymorphisms than in those who had the major homozygous genotype, even after conservative Bonferroni adjustment for multiple comparisons (p = 0.03, 0.024, respectively). These results are comparable with the previous reports in Caucasians 16,17,[20][21][22] . Further, we extended this finding to basal CRP level according to haplotype, and found that the basal level of CRP was lower in haplotype ht1[TACGCA] containing major alleles of CRP -390 and 2043, while it was higher in haplotype ht4 [TATGTG] containing minor alleles of CRP -390 and 2043, although the significance disappeared with Bonferroni adjustment.…”
Section: Discussionsupporting
confidence: 92%
“…We also examined whether these polymorphisms had any effect on serum CRP levels, and found that basal levels of CRP were significantly higher in individuals who had minor allele in -390 C>A or T and 2043 A>G polymorphisms than in those who had the major homozygous genotype, even after conservative Bonferroni adjustment for multiple comparisons (p = 0.03, 0.024, respectively). These results are comparable with the previous reports in Caucasians 16,17,[20][21][22] . Further, we extended this finding to basal CRP level according to haplotype, and found that the basal level of CRP was lower in haplotype ht1[TACGCA] containing major alleles of CRP -390 and 2043, while it was higher in haplotype ht4 [TATGTG] containing minor alleles of CRP -390 and 2043, although the significance disappeared with Bonferroni adjustment.…”
Section: Discussionsupporting
confidence: 92%
“…Twin and family studies observe substantial heritability (20-40 percent) for CRP levels 5,6 . Common and functional polymorphisms in the CRP gene have consistently been associated with inter-individual differences in plasma CRP levels 7,8 . Recently, Lange, et al reported that, among persons at risk for a first MI or stroke, several common variants in the CRP gene were associated with increased relative risk of cardiovascular events in the Cardiovascular Health Study (CHS), a longitudinal cohort study of adults over the age of 65 9 .…”
mentioning
confidence: 99%
“…33 Within the promoter, several polymorphisms were discovered in transcription factor binding E-box sites, all of which Autologous ligands include native and modified plasma lipoproteins, damaged cell membranes, different phospholipids and related compounds, small nuclear ribonucleoprotein particles, and apoptotic cells. 34,35,36 Extrinsic ligands include many glycan, phospholipid, and other constituents of microorganisms, such as capsular and somatic components of bacteria, fungi, and parasites, as well as plant products.…”
Section: Crp Gene Regulationmentioning
confidence: 99%